Oral conditions of pediatric patients with Williams-Beuren syndrome: two case reports - Pires, Flávia Silva; Paula, Viviane Andrade Cancio; Faker, Khawana; Di Lanaro, Natalia; Carvalho, Raissa Christiane O de; Tostes, Mônica Almeida (Brazilian Dental Science, 2019)
Objective: The objective of this paper was to describe the oral conditions of two children accompanied by their mothers who reported to the Department of Pediatric Dentistry of Fluminense Federal University with Williams-Beuren syndrome (WBS). Case report: The 9-year-old female patient had a family and medical history significant for placental abruption, caesarean section, delayed psychomotor development, learning disabilities, tendency to selfdistract and congenital heart disease. In contrast, the 7-year-old male patient had a normal birth and no gestational intercurrences. Discussion: Clinically, the female presented with mixed dentition, crowding in the maxillary and mandibular arches, prolonged retention of deciduous teeth, anterior and posterior cross-bite and Angle Class I malocclusion, while the male had mixed dentition and retarded psychomotor development. Due to the patients having congenital heart disease, a prophylactic antibiotic regimen was prescribed prior to the dental procedures in both of them. Conclusion: These patients had been followed up for 2 years and this case report underscores the importance of early dental evaluation and counselling for parents of WBS patients. Keywords Williams Beuren syndrome; Oral manifestations; Child.